SYSTEMATIC LITERATURE REVIEW PENGARUH SHOPPING LIFESTYLE DAN HEDONIC SHOPPING MOTIVATION TERHADAP IMPULSE BUYING PADA KONSUMEN MARKETPLACE ATAU E-COMMERCE - Ramdhan, Muhamad; Rahmantya, Yanneri Elfa Kiswara (Jurnal Ilmiah Global Education, 2023)
Advances in information and communication technology are utilized by business service providers marketplace or e-commerce. In order to be able to compete in selling a product or item that is owned, so that business people continue to make the best strategy to see the behavior of their consumer. So, a review is needed journal papers discussing roles shopping lifestyle and hedonic shopping motivation to impulse buying. The method used in this research is Systematic Literature Review (SLR) for journal papers published from 2018-2023. There are two Research Question (RQ) set in this study. Research focuses on producer who sell their products or goods through marketplace or e-commerce. So that the results obtained in this study are expected to provide information so that online business people can find out how consumer behavior is and can improve or set strategies to increase sales of these products or goods.